BRAND WHEEL OR THE SPECIFICS OF EVALUATING THE EFFECTIVENESS OF AN ORGANIZATION'S PR ACTIVITIES - Aslanova, Aziza (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
In the modern era of internet and digital economy development, the demand for effective use of digital PR in both daily life and business is growing. This article discusses the key aspects of digital PR in the context of branding and promoting products and services. Digital PR is becoming an integral part of business strategy, as companies are forced to use the internet and social media to advertise their products, engage with customers, and drive sales. A crucial aspect of digital PR is changing the nature of brand-consumer relations. While the fundamental principles of information exchange and positive brand image formation are preserved, this process is taking on new forms and tools. The article examines the branding promotion activities of the Ministry of Higher Education, Science, and Innovation of the Republic of Uzbekistan. It analyzes survey results conducted on two different platforms. As a result, it was found that the effectiveness of digital PR not only enhances the communicative activity of the brand but also allows the organization to quickly adapt to changing demands and improve competitiveness.
Keywords: government organization; branding; state image; brand wheel; brand sociology; digital PR